2012
DOI: 10.1007/s00234-012-1114-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and radiological results of endovascular internal trapping in vertebral artery dissection

Abstract: 2 Abstract PurposePrevious reports have suggested that endovascular parent artery occlusion is an effective and safe procedure for the treatment of vertebral artery dissection (VAD). However, the results of long-term outcomes are still unclear. This study reviewed the clinical and imaging outcomes of patients with VAD treated by endovascular internal trapping. MethodsA total of 73 patients were treated for VAD by endovascular internal trapping between March 1998 and March 2011. Patients were regularly followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 20 publications
2
42
0
1
Order By: Relevance
“…In studies including only patients who qualifi ed for endovascular treatment, lower mortality rates (5-9%) were reported, which is not surprising given that these studies excluded the most severe patients from the outset. 35,41 Mortality outcome in patients without subarachnoid haemorrhage is low and similar to that in patients with cervical artery dissection, ranging between none and 3% in reported series.…”
Section: Mortalitysupporting
confidence: 75%
See 2 more Smart Citations
“…In studies including only patients who qualifi ed for endovascular treatment, lower mortality rates (5-9%) were reported, which is not surprising given that these studies excluded the most severe patients from the outset. 35,41 Mortality outcome in patients without subarachnoid haemorrhage is low and similar to that in patients with cervical artery dissection, ranging between none and 3% in reported series.…”
Section: Mortalitysupporting
confidence: 75%
“…Sometimes, endovascular treatment is undertaken if the dissecting aneurysm has increased in size, to prevent rupture, or more rarely to reduce signs of brainstem com pression. 21,35,88,89 In children, the preferred and widespread practice is surgical or endovascular treatment in patients with intracranial artery dissection with subarachnoid haemorrhage and those without subarachnoid haemorrhage and masseff ect, whereas patients with intracranial artery dissection without subarachnoid haemorrhage and cerebral ischaemia tend to be given medical treatment. …”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ischemic complications are the result of occlusion and ischemia of perforating arteries and the anterior spinal artery. 13 In a series of 72 patients treated with deconstructive techniques, Kashiwazaki et al 13 reported 2 cases of spinal cord infarction and 7 cases of partial Wallenberg syndrome secondary to occlusion of vertebrobasilar dissecting aneurysms involving the PICA. Despite these perforator complications, only 1 patient died and the remaining patients had mRS Յ2.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although there have been recent reports documenting the effectiveness of stent-assisted coil embolization or flow diverter stent placement, [8][9][10] but parent artery occlusion remains as a safe and effective treatment, particularly in the acute phase of rupture. 11,12) To minimize the risk of re-hemorrhage and developing cerebral infarction following parent artery occlusion, it is important to make a strategy based on the location of the lesion relating to the posterior inferior cerebellar artery (PICA) origin.…”
Section: Introductionmentioning
confidence: 99%